Transient volume water content analysis of unsaturated soil slopes considering two-dimensional rainfall infiltration - FU Jian-xin; SONG Wei-dong; DU Jian-hua (工程科学学报)
Rainfall is one of the key factors of unsaturated soil slope instability and the strength of unsaturated soils is closely related to volume water content. Considering two-dimensional rainfall infiltration, on the basis of the Darcy seepage theorem and mass conservation law of unsaturated soils, this paper constructed a two-dimensional infiltration model of unsaturated soils and coded a MATLAB program based on an alternating-direction-implicit (ADI) finite difference method which is used to numerical calculations to study the transient volume water content distribution at different slope locations under different rainfall conditions. The results show that the volume water content changes with the horizontal distance and depth. Moreover, the volume water content at the slope surface changes far greater than that at the deep part. The smaller the initial volume water content is, the greater the change in volume water content of the slope is, which is disadvantageous to slope stability.